Self-thermal-insulation wall material based on solid waste and preparation method of self-thermal-insulation wall material

By using ceramic tile polishing waste, granite powder and calcium carbide slag to prepare self-insulating wall materials, the existing technology problems of out-of-sync service life and poor fire resistance between the insulation layer and the solid wall are solved, and efficient resource utilization of solid waste is achieved. utilization and green building development.

CN119349923APending Publication Date: 2025-01-24YANGTZE NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411443224.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the existing building enclosure structure, the service life of the insulation layer and the solid wall are not synchronized, and the insulation layer is mostly organic material, resulting in complex construction, long construction time and poor fire resistance, which limits the development of green buildings.

Method used

The three solid wastes of tile polishing waste, granite powder, and stone residue are used as raw materials, and the self -insulation wall materials are prepared through the process of mechanical ball grinding, granularity, trapped materials, molding, and water and water steaming pressure.

Benefits of technology

It achieves efficient resource utilization of solid waste, has a short production cycle and low energy consumption. The mechanical properties and thermal properties of the material meet the standards of sintered self-insulating wall materials, and the risk of building fire protection is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349923A_ABST
    Figure CN119349923A_ABST
Patent Text Reader

Abstract

The invention discloses a solid waste-based self-insulation wall material and a preparation method thereof, and the preparation method comprises the steps of proportioning, mixing, granulating, ageing, forming, hydrothermal autoclaving and the like. Wherein in the proportioning process, the ceramic tile polishing waste, the granite powder and the carbide slag are proportioned according to the weight part ratio of (21.0-28.0): (21.0-28.0): (44.0-58.0). The method has the remarkable effects that the three solid wastes, namely the granite powder, the ceramic tile polishing waste and the carbide slag, are completely used as raw materials for preparing the self-heat-preservation wall body material, so that the resource utilization of the solid wastes can be realized to a great extent, and the sustainable development of resources is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building material production, and in particular to a self-insulating wall material based on solid waste and a preparation method thereof. Background Art

[0002] The building envelope (mainly the exterior wall) is composed of a thermal insulation layer and a solid wall. Figure 1 As shown. At present, most of the building envelope structures in my country adopt the external wall insulation technology with the insulation layer compounded outside the solid wall or the external wall insulation technology with the insulation layer compounded inside the solid wall. Due to the complex structure of the insulation layer and the wall system, the construction process is increased and the construction time is extended. It is difficult for the insulation layer to achieve the same life as the building. In addition, the insulation layer is mostly made of organic materials, which will bring certain difficulties to the fire protection of the building and greatly restrict the development of green buildings.

[0003] Among them, the exterior wall self-insulation technology is a new technology that uses inorganic materials with good thermal insulation performance directly as masonry materials to build walls, so that the thermal performance of the building's exterior wall itself meets the building energy-saving design standards. It has unique advantages and broad prospects: First, the exterior wall self-insulation technology completely solves the problem of the service life of the insulation layer and the solid wall being out of sync, eliminating the trouble of replacing insulation materials. Secondly, the use of self-insulating wall materials made of inorganic materials completely avoids the problem of building fire prevention and can provide a safer living environment. Finally, self-insulating wall materials can also utilize solid waste to a certain extent, which has a promoting effect on the recycling of resources. However, the utilization of many solid wastes is still in a relatively early stage, especially tile polishing waste, granite powder and calcium carbide slag.

[0004] As a popular building material, ceramic tiles are widely used in the building decoration industry. In the ceramic tile manufacturing process, in order to achieve the required flatness, thickness and glossiness, the fired ceramic tiles are polished to remove a 0.4 to 0.8 mm thick surface layer. This process produces an industrial solid waste called ceramic tile polishing waste. 2 Ceramic tiles generate about 0.6 to 0.8 kg of tile polishing waste. At present, tile polishing waste is mainly disposed of by landfill, but this often leads to secondary pollution, such as air dust pollution during transportation and groundwater pollution caused by landfill leakage. This environmental pollution not only endangers ecological safety, but also hinders the sustainable development of the ceramic tile industry. Therefore, it is crucial to effectively utilize tile polishing waste.

[0005] Sand and gravel are the most basic and important building materials in engineering construction. However, natural sand and gravel resources are increasingly scarce, and the country strictly restricts river mining. Therefore, artificial sand and gravel have become the main source of raw materials for domestic engineering construction. The production process of artificial sand and gravel requires crushing, which will produce a large amount of stone powder. Because of its fine particle size, open-air stacking will cause dust pollution to the environment, so it needs to be treated. At present, the more mature treatment method is backfilling or using it as a concrete admixture. Stone powder can be divided into limestone powder, granite powder and marble powder according to its composition. The chemical composition of limestone powder and marble powder is mainly CaCO 3 , while granite powder is mainly SiO 2 At present, calcareous stone powder (limestone powder and marble powder) is well used in concrete, while siliceous stone powder (granite powder) will affect the workability and durability of concrete, and its application is not ideal.

[0006] Carbide slag is a solid waste generated during the production of acetylene chemicals. It can be disposed of by regular stacking such as land reclamation and ditch filling, and then sold after natural sedimentation, or by replacing limestone products. However, these methods have some disadvantages, such as large land occupation, serious pollution, unstable treatment effect, and not as popular as limestone products in the building materials market.

[0007] Therefore, if tile polishing waste, granite powder and carbide slag are used as the main raw materials to develop solid waste-based self-insulating wall materials, the resource utilization of solid waste can be achieved, the sustainable development of resources can be realized, and the high-quality development of green buildings can be promoted. Summary of the invention

[0008] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a self-insulating wall material based on solid waste and a preparation method thereof. The raw materials are completely composed of three types of solid waste: granite powder, tile polishing waste and carbide slag. The resource utilization of solid waste can be realized to the greatest extent, and the sustainable development of resources can be achieved.

[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] In a first aspect, a method for preparing a self-insulating wall material based on solid waste comprises the following steps:

[0011] Step 1, batching process: batching tile polishing waste, granite powder and carbide slag according to the weight ratio of (12.5-37.5): (12.5-37.5): (44.0-58.0);

[0012] Step 2, mixing process: the raw materials obtained by the batching are co-grinded by a mechanical spheroidal graphite process, and a PVA aqueous solution accounting for 10wt% of the total mass of the raw materials is added during the co-grinding process, and mixed evenly;

[0013] Step 3, granulation process: granulate the raw materials mixed evenly in step 2 by a granulator to make the particle size distribution between 0.2 and 2.0 mm;

[0014] Step 4, material trapping process: plastic-sealing the granulated raw materials and letting them stand for material trapping;

[0015] Step 5, forming process: pressing the trapped raw materials into semi-finished thermal insulation material blocks of required size;

[0016] Step 6, hydrothermal autoclaving process: placing the semi-finished thermal insulation material building blocks into a reactor for hydrothermal autoclaving to obtain finished thermal insulation material building blocks.

[0017] Further, in step 1, the SiO 2 The weight percentage is not less than 60%, and the particle size is 0.5-50μm; the SiO 2 The weight percentage of CaO in the carbide slag is not less than 60%, and the particle size is 0.5-50μm; the weight percentage of CaO in the carbide slag is not less than 60%, and the particle size is 0.5-100μm.

[0018] Furthermore, in step 2, the co-grinding treatment lasts for 6 hours.

[0019] Furthermore, in step 2, the concentration of the PVA aqueous solution is 8 wt %, and the PVA aqueous solution is divided into at least two portions, and one portion of the PVA aqueous solution is added to the raw material and mixed evenly, and then the other portion of the PVA aqueous solution is added.

[0020] Furthermore, the duration of the trapped material treatment in step 4 is 10-14 hours.

[0021] Furthermore, the pressure of the pressing process in step 5 is 20-30 MPa.

[0022] Furthermore, the heating rate of the hydrothermal autoclave in step 6 is ≤5°C / min, the insulation temperature is 105-175°C, the insulation time is 8-12 hours, and the pressure is 0.5-5MPa.

[0023] In the second aspect, the present invention also proposes a self-insulating wall material based on solid waste, which is prepared by the preparation method described in the first aspect, including ceramic tile polishing waste, granite powder and carbide slag in a weight ratio of (12.5-37.5): (12.5-37.5): (44.0-58.0).

[0024] Furthermore, the SiO in the tile polishing waste 2 The weight percentage is not less than 60%, and the particle size is 0.5-50μm; the SiO 2The weight percentage of CaO in the carbide slag is not less than 60%, and the particle size is 0.5-50μm; the weight percentage of CaO in the carbide slag is not less than 60%, and the particle size is 0.5-100μm.

[0025] The remarkable effects of the present invention are:

[0026] 1. Large-scale resource utilization of solid waste: In the past, only a small amount of solid waste could be added to building materials, while the raw materials of the present invention are completely composed of three types of solid waste: granite powder, tile polishing waste and carbide slag, which can realize the resource utilization of solid waste to a great extent and achieve sustainable development of resources;

[0027] 2. Strong comprehensive performance: The mechanical properties and thermal properties of the present invention basically reach the standards of sintered self-insulating wall materials, which are much higher than those of non-sintered self-insulating wall materials;

[0028] 3. Low energy consumption: The temperature of hydrothermal autoclaving does not exceed 180°C, which is much lower than the preparation temperature of sintered self-insulating wall materials, and the energy consumption is close to that of non-sintered self-insulating wall materials;

[0029] 4. Short production cycle: The hydrothermal autoclave time does not exceed 12 hours, and the entire production cycle does not exceed 3 days, which is much shorter than the production cycle of existing self-insulating wall materials;

[0030] 5. Simple process: Compared with non-sintered self-insulating wall materials, the raw materials of the present invention do not require gas generating agents and foam stabilizers, and do not require maintenance. Compared with sintered self-insulating wall materials, the raw materials of the present invention do not require pore-forming agents, and do not require brick shape and hole shape design. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of a building enclosure structure in the prior art;

[0032] Figure 2 is a flow chart of the method of the present invention;

[0033] Figure 3 is a microstructure diagram of a sample obtained in Example 1 of the present invention;

[0034] Figure 4 is a microstructure diagram of a sample obtained in Example 2 of the present invention;

[0035] Figure 5 is a microstructure diagram of a sample obtained in Example 3 of the present invention;

[0036] Figure 6 is a microstructure diagram of a sample obtained in Example 4 of the present invention;

[0037] Figure 7 is a microstructure diagram of a sample obtained in Example 5 of the present invention;

[0038] Figure 8 This is a microstructure diagram of the sample obtained in Example 6 of the present invention. DETAILED DESCRIPTION

[0039] The specific implementation manner and working principle of the present invention are further described in detail below with reference to the accompanying drawings.

[0040] The inventor of the present application has found that in the prior art, there are mainly two types of self-insulating wall materials, one is non-sintered self-insulating wall materials, such as autoclaved aerated concrete, lightweight aggregate concrete and gypsum products, and the other is sintered self-insulating wall materials, such as sintered porous bricks, shale sintered hollow blocks, ceramsite self-insulating blocks, etc. The advantages and disadvantages of the two self-insulating wall materials are as follows:

[0041] 1. Non-sintered self-insulating wall materials

[0042] advantage:

[0043] (1) Lightweight: Non-sintered self-insulating wall materials usually have a lower density, which helps to reduce the weight of the building and reduce the burden on the foundation and structure.

[0044] (2) Energy saving and environmental protection: Strength can be obtained through hydration of cementitious materials without the need for high-temperature sintering. The energy consumption required for production is low, which can reduce the impact on the environment.

[0045] (3) Simple preparation process: Compared with sintered materials, the production process of non-sintered self-insulating wall materials is simpler and easier to mass produce.

[0046] shortcoming:

[0047] (1) High heat transfer coefficient: Cement-based materials such as autoclaved aerated concrete and lightweight aggregate concrete have high heat transfer coefficients, usually between 0.10 and 0.35 W·(m·K) -1 It is impossible to meet the higher standards of building energy conservation requirements.

[0048] (2) Low compressive strength: The compressive strength of the product is relatively low, usually not exceeding 5MPa, and is not suitable for load-bearing structures.

[0049] (3) Poor water resistance: Gypsum products cannot meet the durability requirements in high humidity environments when used as exterior walls.

[0050] (4) Long production cycle: For cement-based products, it takes a long period of time for cement hydration to gain strength (curing age ≥ 7 days).

[0051] (5) Restrictions on raw material selection: The selection of solid waste raw materials is quite picky. The pH value, impurity content, etc. will limit the utilization of solid waste, and the amount that can be added is relatively limited.

[0052] 2. Sintered self-insulating wall material

[0053] advantage:

[0054] (1) Good thermal insulation effect: Through the brick type and hole type design, the thermal conductivity of sintered self-insulating wall material products is low, and can meet the design requirements of building energy saving of more than 65% when used alone.

[0055] (2) High strength: The high-temperature sintering process can achieve higher strength, which is suitable for use in load-bearing parts of buildings.

[0056] (3) Good water resistance: Sintered self-insulating wall material products have excellent water resistance, which helps to ensure the durability of the wall.

[0057] (4) Solid waste can be fully utilized: The organic matter in industrial solid waste can be fully burned and consumed through the sintering process, and the heavy metals in the solid waste can also be effectively solidified through the sintering reaction, avoiding the dissolution of heavy metal ions and ensuring environmental safety.

[0058] shortcoming:

[0059] (1) High production energy consumption: Sintered self-insulating wall materials need to be sintered at high temperatures (≥900°C), which consumes a lot of energy and produces certain harmful gases.

[0060] (2) Long production cycle: The sintering process includes heating, insulation and cooling processes, which takes a long time (≥3 days), resulting in a long production cycle.

[0061] In order to overcome the defects of the two existing self-insulating wall materials, the present invention proposes a self-insulating wall material based on solid waste, which is prepared by mixing ceramic tile polishing waste, granite powder and calcium carbide slag in a weight ratio of (12.5-37.5): (12.5-37.5): (44.0-58.0). 2 The weight percentage is not less than 60%, and the particle size is 0.5-50μm; the SiO 2 The weight percentage of CaO in the carbide slag is not less than 60%, and the particle size is 0.5-50μm; the weight percentage of CaO in the carbide slag is not less than 60%, and the particle size is 0.5-100μm.

[0062] When the composition of wall self-insulating materials is certain, the number of holes in the material (porosity) determines the mechanical properties and thermal properties of the wall insulation materials. Since the thermal conductivity of air is much lower than that of various building materials, the more holes in the material and the higher the porosity, the lower the thermal conductivity of the material and the better the thermal insulation performance. However, the higher the porosity, the looser the structure of the material, resulting in reduced strength. If the wall insulation material wants to obtain better mechanical properties and is used as a self-insulating wall material, the structure must be denser, which will inevitably require sacrificing more thermal insulation performance. For example, the thermal conductivity of B03 autoclaved aerated concrete blocks can be as low as 0.1W·(m·K) -1 However, its strength can only reach A1.0 level (1.0MPa). Therefore, it is difficult to find a balance between strength and thermal insulation performance in existing self-insulating wall materials.

[0063] The inventor of this patent application has found that the main components of tile polishing waste and granite powder are SiO 2 , the main component of carbide slag powder is CaO. 2 Mixed with CaO in a certain proportion, and then subjected to hydrothermal reaction at appropriate temperature and pressure, totobemorite can be generated, with a chemical composition of 5CaO·6SiO·nH 2 O. In the complete crystallization state, tobermorite is a layered calcium silicate mineral with high strength and compact structure. However, by adjusting the preparation process, lowering the temperature and pressure, tobermorite can be incompletely crystallized to generate whiskers with a relatively high aspect ratio. The interlaced whiskers can form a porous structure. At the same time, at room temperature, SiO 2 , CaO and H 2 O can react to form calcium silicate hydrate, the chemical composition of which is 3CaO·2SiO·nH 2 O, Calcium silicate hydrate is an important hydration product in cement-based materials, and it plays an important role in the strength of cement-based materials.

[0064] Therefore, according to the chemical composition of tobermorite and calcium silicate hydrate, the calcium-silicon ratio (CaO / SiO 2The molar ratio of calcium silicate to silicate is set between 5 / 6-3 / 2 (converted to a mass ratio of 0.78-1.40), ensuring that the raw material particle size is at the same order of magnitude, setting the temperature of hydrothermal autoclaving between 105-175°C, the time between 8-12h, and the pressure between 0.5-5MPa, which can ensure that the generated product will have both tobermorite and hydrated calcium silicate. Among them, the whisker-like tobermorite is mainly responsible for pore formation and provides a certain strength, while the hydrated calcium silicate gelling can gel the tobermorite whiskers more firmly and provide the main strength of the material, so that the self-insulating wall material has excellent strength and thermal insulation performance at the same time. Moreover, by controlling the calcium-silicon ratio, temperature, pressure and time, the amount and degree of crystallization of hydrated calcium silicate gelling and tobermorite whiskers can be controlled, and the strength and thermal insulation performance of the self-insulating wall material can be regulated to a certain extent.

[0065] In view of this, the present invention proposes a method for preparing a self-insulating wall material based on solid waste, such as Figure 1 As shown, the following steps are included:

[0066] Step 1, batching process: the raw materials used are all existing industrial solid wastes, and the chemical composition (wt%) of the tile polishing waste is SiO 2 >60.0, particle size is 0.5-50μm. The chemical composition (wt%) of granite powder is SiO 2 >60, particle size is 0.5-50μm, the chemical composition (wt%) of carbide slag is CaO>60%, particle size is 0.5-100μm. The ingredients are prepared according to the raw material ratio shown in Table 1:

[0067] Table 1 Raw material ratio (wt%)

[0068]

[0069] Step 2, mixing process: the prepared raw materials are co-milled for 6 hours by mechanical ball milling process. During the co-milling process, a PVA aqueous solution accounting for 10wt% of the total mass of the raw materials is added, and the concentration is 8wt%. First, half of the PVA aqueous solution is added to the co-milled raw materials, and the other half is added after fully mixing, and the raw materials and the PVA aqueous solution are fully rolled again to be evenly mixed;

[0070] Step 3, granulation process: the raw materials mixed evenly in step 2 are granulated by a granulator, and the particle size distribution is between 0.2 and 2.0 mm after completion;

[0071] Step 4, material trapping process: the granulated raw materials are sealed and left to stand for 12 hours;

[0072] Step 5, forming process: using a press at 20-30MPa to press the trapped raw materials into semi-finished thermal insulation blocks of required size;

[0073] Step 6, hydrothermal autoclave process: put the semi-finished insulation material block into a reactor for hydrothermal autoclave, with a heating rate of ≤5°C / min, a holding temperature of 105-175°C, a holding time of 8-12 hours, and a pressure of 0.5-5MPa to obtain a finished insulation material block.

[0074] The specific embodiments of the above preparation method are as follows:

[0075] Embodiment 1:

[0076] (1) preparing a solid waste-based self-insulating wall material, the raw materials used comprising carbide slag, granite powder and tile polishing waste, wherein:

[0077] The calcium carbide slag is a fine powder with a chemical composition (wt%) of CaO=75.5, SiO 2 =8.2,Al 2 O 3 =6.5,Fe 2 O 3 =1.9, SO 3 =1.2, loss on ignition =6.7, particle size d 10 =4.3μm, d 50 =17.1μm, d 90 =45.3μm;

[0078] Granite powder is fine powder, chemical composition (wt%) is SiO 2 =71.5,Al 2 O 3 =15.7, K 2 O=3.3,CaO=2.6,Na 2 O=2.3,Fe 2 O 3 =1.1, loss on ignition =3.5, particle size d 10 =8.0μm, d 50 =35.5μm, d 90 =89.3μm;

[0079] The ceramic tile polishing waste is a fine powder with a chemical composition (wt%) of SiO 2 =66.4,Al 2 O 3 =20.7, K 2 O=3.1,Na 2 O = 2.2, CaO = 1.6, ignition loss = 6.0, particle size d 10 =2.5μm, d 50=8.1μm, d 90 =29.3 μm. The raw materials were prepared according to the raw material ratio shown in Table 2.

[0080] Table 2 Raw material ratio (wt%)

[0081]

[0082] (2) Sample 1 was prepared according to the mixing process, granulation process, material trapping process, molding process, drying process and hydrothermal positive pressure process described in steps 2 to 6 of the above preparation method; wherein the heating rate of the hydrothermal autoclave process was 4°C / min, the holding temperature was 150°C, the pressure was 2.0 MPa, and the holding time was 10 h.

[0083] (3) Performance testing

[0084] The prepared sample 1 was subjected to a performance test, and the test results are shown in Table 3:

[0085] Table 3 Sample properties

[0086]

[0087] It can be seen from Table 3 that the thermal conductivity of sample 1 is only 0.12 W·(m·K) -1 , close to the thermal conductivity of B04 autoclaved aerated concrete (<0.12W·(m·K) -1 ), but the strength of B04 autoclaved aerated concrete is only A2.0 (2.0MPa), while the compressive strength of sample 1 is as high as 21.5MPa, which has reached the strength grade of masonry brick MU20 and can be used as a partial load-bearing structure.

[0088] (4) Microscopic morphology

[0089] Figure 3 This is the microstructure of Sample 1. It can be seen that Sample 1 mainly has two structures: whiskers and gel clusters. The whisker-like tobermorite forms a porous structure by interlacing with each other, which improves the thermal insulation performance of Sample 1. The hydrated calcium silicate gel cluster can gel the tobermorite whiskers more firmly, thereby improving the strength of Sample 1.

[0090] Embodiment 2:

[0091] (1) The raw materials used in this example are exactly the same as those in Example 1, except that the raw materials are prepared according to the ratio shown in Table 4.

[0092] Table 4 Raw material ratio (wt%)

[0093]

[0094] (2) Sample 2 was prepared according to the mixing process, granulation process, material trapping process, molding process, drying process and hydrothermal positive pressure process described in steps 2 to 6 of the above preparation method, wherein the heating rate of the hydrothermal autoclave process was 3°C / min, the holding temperature was 170°C, the pressure was 1.5 MPa, and the holding time was 8 h.

[0095] (3) Performance testing

[0096] The prepared sample 2 was subjected to a performance test, and the test results are shown in Table 5:

[0097] Table 5 Sample performance

[0098]

[0099] It can be seen from Table 5 that the thermal conductivity of sample 2 is only 0.059 W·(m·K) -1 The thermal performance is significantly better than the existing inorganic wall insulation materials. At the same time, the strength can reach 15.6MPa, reaching the strength grade of MU15 wall bricks, and can be used as a partial load-bearing structure.

[0100] (4) Microscopic morphology

[0101] Figure 4 The microstructure of sample 2 shows that sample 2 mainly has two structures: whiskers and gel groups. The whisker-like tobermorite forms a porous structure by interlacing with each other, which improves the thermal insulation performance of sample 2. The hydrated calcium silicate gel group can gel the tobermorite whiskers more firmly, thereby improving the strength of sample 2. At the same time, the size of the hydrated calcium silicate gel group is small, so the strength of sample 2 is lower than that of sample 1.

[0102] Embodiment 3:

[0103] (1) The raw materials used in this embodiment are the same as those in Example 1, except that the raw materials are prepared according to the raw material ratio shown in Table 6.

[0104] Table 6 Raw material ratio (wt%)

[0105]

[0106] (2) Sample 3 was prepared according to the mixing process, granulation process, material trapping process, molding process, drying process and hydrothermal positive pressure process described in steps 2 to 6 of the above preparation method, wherein the heating rate of the hydrothermal autoclave process was 3.5°C / min, the holding temperature was 140°C, the pressure was 2.5MPa, and the holding time was 12h.

[0107] (3) Performance testing

[0108] Table 7 Sample performance

[0109]

[0110] It can be seen from Table 7 that the thermal conductivity of sample 3 is increased to 0.15 W·(m·K) -1 The thermal performance is slightly reduced, but the strength is as high as 31.2MPa, which has reached the strength grade of MU30 wall bricks and can be used as a load-bearing structure.

[0111] (4) Microscopic morphology

[0112] Figure 5 The microstructure of sample 3 shows that the product is mainly a hydrated calcium aluminate gel mass, with only a small amount of whisker-shaped tobermorite. Because the temperature of hydrothermal autoclaving is low, it is not conducive to the formation of tobermorite whiskers, and the pore-forming effect is poor, so the thermal insulation performance of sample 3 is reduced. However, because the hydrothermal autoclaving is maintained for a longer time than in Examples 1 and 2, and the pressure is higher, the generated hydrated calcium aluminate gel is relatively complete and evenly distributed, and the structure is more compact, thereby significantly increasing the compressive strength of sample 3.

[0113] Embodiment 4:

[0114] (1) Preparation of self-insulating wall materials, the raw materials used include carbide slag, granite powder and tile polishing slag, wherein:

[0115] The calcium carbide slag is a fine powder with a chemical composition (wt%) of CaO=72.2, SiO 2 =7.2,Al 2 O 3 =6.9,Fe 2 O 3 =4.4, SO 3 =2.0, loss on ignition =7.3, particle size d 10 =6.7μm, d 50 =19.2μm, d 90 =40.1μm;

[0116] Granite powder is fine powder, chemical composition (wt%) is SiO 2 =69.5,Al 2 O 3 =16.2, CaO=3.9, Na 2 O=3.2,K 2 O=2.7,Fe 2 O 3 =1.9, loss on ignition =5.3, particle size d 10 =7.2μm, d 50 =31.1μm, d 90 =79.8μm;

[0117] The ceramic tile polishing residue is a fine powder, and its chemical composition (wt%) is SiO 2 =70.1,Al 2 O 3 =18.4, K 2 O=2.8,Na 2 O = 2.4, CaO = 2.1, ignition loss = 4.2, particle size d 10 =2.8μm, d 50 =8.7μm, d 90 =32.2 μm. The raw materials were prepared according to the raw material ratio shown in Table 8.

[0118] Table 8 Preparation formula (wt%)

[0119]

[0120] (2) Sample 4 was prepared according to the mixing process, granulation process, material trapping process, molding process, drying process and hydrothermal positive pressure process described in steps 2 to 6 of the above preparation method; wherein the heating rate of the hydrothermal autoclave process was 4°C / min, the holding temperature was 170°C, the pressure was 1.5MPa, and the holding time was 8h.

[0121] (3) Performance testing

[0122] The prepared sample 4 was subjected to performance tests, and the test results are shown in Table 9:

[0123] Table 9 Sample performance

[0124]

[0125] It can be seen from Table 9 that the overall performance of Sample 4 is relatively close to that of Example 2, with a thermal conductivity of only 0.061 W·(m·K)-1, and thermal performance significantly better than existing inorganic wall insulation materials. At the same time, the strength can reach 15.8 MPa, which also reaches the strength grade of masonry brick MU15, and can be used as a partial load-bearing structure.

[0126] (4) Microscopic morphology

[0127] Figure 6 The microstructure of sample 4 shows that sample 4 mainly has two structures: whiskers and gel groups. The whisker-like tobermorite forms a porous structure by interlacing with each other, so that sample 4 has better thermal insulation performance. At the same time, the hydrated calcium silicate gel group can gel the tobermorite whiskers together, ensuring the strength of sample 4.

[0128] Embodiment 5:

[0129] (1) The raw materials used in this example are the same as those in Example 4, except that the raw materials are prepared according to the raw material ratio shown in Table 10.

[0130] Table 10 Raw material ratio (wt%)

[0131]

[0132] (2) Sample 5 was prepared according to the mixing process, granulation process, material trapping process, molding process, drying process and hydrothermal positive pressure process described in steps 2 to 6 of the above preparation method; wherein the heating rate of the hydrothermal autoclave process was 4°C / min, the holding temperature was 170°C, the pressure was 1.5MPa, and the holding time was 8h.

[0133] (3) Performance testing

[0134] The prepared sample 5 was subjected to a performance test, and the test results are shown in Table 11:

[0135] Table 11 Sample performance

[0136]

[0137] It can be seen from Table 11 that the overall performance of Sample 5 is relatively close to that of Example 2, with a thermal conductivity of only 0.06 W·(m·K)-1, and thermal performance significantly better than existing inorganic wall insulation materials. At the same time, the strength can reach 15.5 MPa, which also reaches the strength grade of wall brick MU15, and can be used as a partial load-bearing structure.

[0138] (4) Microscopic morphology

[0139] Figure 7 Figure 5 is the microstructure of sample 5. It can be seen that sample 5 mainly has two structures: whiskers and gel groups. The whisker-like tobermorite forms a porous structure by interlacing with each other, so that sample 5 has better thermal insulation performance. At the same time, the hydrated calcium silicate gel group can gel the tobermorite whiskers together, ensuring the strength of sample 5.

[0140] Embodiment 6:

[0141] (1) The raw materials used in this example are the same as those in Example 4, except that the raw materials are prepared according to the raw material ratio shown in Table 12.

[0142] Table 12 Raw material ratio (wt%)

[0143]

[0144] (2) Sample 6 was prepared according to the mixing process, granulation process, material trapping process, molding process, drying process and hydrothermal positive pressure process described in steps 2 to 6 of the above preparation method; wherein the heating rate of the hydrothermal autoclave process was 4°C / min, the holding temperature was 170°C, the pressure was 1.5MPa, and the holding time was 8h.

[0145] (3) Performance testing

[0146] The prepared sample 6 was subjected to performance tests, and the test results are shown in Table 13:

[0147] Table 13 Sample performance

[0148]

[0149] It can be seen from Table 11 that the overall performance of Sample 6 is relatively close to that of Example 2, with a thermal conductivity of only 0.062 W·(m·K)-1, and thermal performance significantly better than existing inorganic wall insulation materials. At the same time, the strength can reach 15.9 MPa, which also reaches the strength grade of masonry brick MU15, indicating that the change in the ratio of granite powder and tile polishing residue has no significant effect on the performance.

[0150] (4) Microscopic morphology

[0151] Figure 8 The microstructure of sample 6 is shown in FIG. 1 . It can be seen that there is no significant change compared with Examples 4 and 5, indicating that the change in the ratio of granite powder and tile polishing residue has no significant effect on the microstructure.

[0152] In summary, the present invention prepares self-insulating wall materials entirely from three kinds of solid wastes, namely granite powder, tile polishing waste and carbide slag, as raw materials, which can not only realize the resource utilization of solid waste to a great extent and achieve sustainable development of resources; but also the mechanical properties and thermal properties of the self-insulating wall materials obtained basically reach the standards of sintered self-insulating wall materials, which are much higher than non-sintered self-insulating wall materials; at the same time, the temperature of hydrothermal autoclaving in the preparation method does not exceed 180°C, which is much lower than the preparation temperature of sintered self-insulating wall materials, and the energy consumption is close to that of non-sintered self-insulating wall materials; at the same time, the production cycle of the entire self-insulating wall material does not exceed 3 days, which is much shorter than the production cycle of existing self-insulating wall materials; in addition, compared with non-sintered self-insulating wall materials, the raw materials of the present invention do not require gas generating agents and foam stabilizers, and do not require maintenance. Compared with sintered self-insulating wall materials, the raw materials of the present invention do not require pore-forming agents, and do not require brick and hole design, and the process is simpler.

[0153] The technical solution provided by the present invention is described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a self-insulating wall material based on solid waste, characterized in that: The steps include: Step 1, batching process: batching tile polishing waste, granite powder and carbide slag according to the weight ratio of (12.5-37.5): (12.5-37.5): (44.0-58.0); Step 2, mixing process: the raw materials obtained by the batching are co-grinded by a mechanical spheroidal graphite process, and a PVA aqueous solution accounting for 10wt% of the total mass of the raw materials is added during the co-grinding process, and mixed evenly; Step 3, granulation process: granulate the raw materials mixed evenly in step 2 by a granulator to make the particle size distribution between 0.2 and 2.0 mm; Step 4, material trapping process: plastic-sealing the granulated raw materials and letting them stand for material trapping; Step 5, forming process: pressing the trapped raw materials into semi-finished thermal insulation material blocks of required size; Step 6, hydrothermal autoclaving process: placing the semi-finished thermal insulation material building blocks into a reactor for hydrothermal autoclaving to obtain finished thermal insulation material building blocks.

2. The method for preparing a self-insulating wall material based on solid waste according to claim 1, characterized in that: In step 1, the weight percentage of SiO2 in the tile polishing waste is not less than 60%, and the particle size is 0.5-50μm; the weight percentage of SiO2 in the granite powder is not less than 60%, and the particle size is 0.5-50μm; the weight percentage of CaO in the carbide slag is not less than 60%, and the particle size is 0.5-100μm.

3. The method for preparing a self-insulating wall material based on solid waste according to claim 1, characterized in that: In step 2, the co-grinding treatment lasts for 6 hours.

4. The method for preparing a self-insulating wall material based on solid waste according to claim 1 or 3, characterized in that: In step 2, the concentration of the PVA aqueous solution is 8 wt %. The PVA aqueous solution is divided into at least two portions, and one portion of the PVA aqueous solution is added to the raw material and mixed evenly, and then the other portion of the PVA aqueous solution is added.

5. The method for preparing a self-insulating wall material based on solid waste according to claim 1, characterized in that: The duration of the trapped material treatment in step 4 is 10-14 hours.

6. The method for preparing a self-insulating wall material based on solid waste according to claim 1, characterized in that: The pressure of the pressing process in step 5 is 20-30MPa.

7. The method for preparing a self-insulating wall material based on solid waste according to claim 1, characterized in that: The heating rate of the hydrothermal autoclave in step 6 is ≤5°C / min, the insulation temperature is 105-175°C, the insulation time is 8-12 hours, and the pressure is 0.5-5MPa.

8. A self-insulating wall material based on solid waste, characterized in that: The ceramic tile polishing waste, granite powder and carbide slag are mixed in a weight ratio of (12.5-37.5): (12.5-37.5): (44.0-58.0) and prepared by the preparation method described in any one of claims 1 to 7.

9. The self-insulating wall material based on solid waste according to claim 8, characterized in that: The weight percentage of SiO2 in the tile polishing waste is not less than 60%, and the particle size is 0.5-50μm; the weight percentage of SiO2 in the granite powder is not less than 60%, and the particle size is 0.5-50μm; the weight percentage of CaO in the carbide slag is not less than 60%, and the particle size is 0.5-100μm.